Modifikasi pelayanan persekutuan dan penelaahan Alkitab dalam penguatan nilai-nilai Pendidikan Agama Kristen: Modifications to Fellowship and Bible Study Services to Strengthen the Values of Christian Religious Education - Benyamin Mofu (IGKOJEI: Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT This community service activity was motivated by the importance of strengthening Christian Religious Education values among children and youth in the church amid social change, technological development, and current challenges in faith formation. This study aimed to describe the implementation of a sermon ministry based on Matthew 27:57-61 during the morning worship service at the Easter Camp of PAR GKI Pengharapan Jayapura and to explain its contribution to strengthening the values of Christian Religious Education. The method used was descriptive qualitative, involving program preparation, literature review, purposive selection of subjects and location, observation of the activity, documentation, and reflective notes. The program was carried out through a morning worship service with the theme “Jesus Remains Present in Every Situation,” delivered to children and youth fellowship participants. The results showed that the sermon ministry in the Easter Camp context functioned as an effective medium for faith formation, not merely as a liturgical activity but also as a contextual space for religious education. The values strengthened through this activity included faith, hope, love, faithfulness, and spiritual resilience. This activity confirms that a sermon ministry based on Matthew 27:57-61 contributes significantly to shaping the spirituality and character of the church’s younger generation and deserves to be developed continuously in church ministry. Keywords: Faith; Gospel; PAK; Spirituality  ABSTRAK Pengabdian kepada masyarakat ini dilatarbelakangi oleh pentingnya penguatan nilai-nilai Pendidikan Agama Kristen bagi anak dan remaja gereja di tengah perubahan sosial, perkembangan teknologi, dan tantangan pembinaan iman pada masa kini. Kegiatan ini bertujuan mendeskripsikan pelaksanaan pelayanan firman Tuhan berbasis Matius 27:57-61 dalam ibadah pagi pada kegiatan Kemping Paskah PAR GKI Pengharapan Jayapura serta menjelaskan kontribusinya terhadap penguatan nilai-nilai Pendidikan Agama Kristen. Metode yang digunakan adalah deskriptif kualitatif dengan tahapan persiapan program, penelaahan literatur, pemilihan subjek dan lokasi secara purposif, observasi pelaksanaan kegiatan, dokumentasi, dan catatan reflektif. Program dilaksanakan dalam bentuk pelayanan ibadah pagi dengan topik “Yesus tetap ada dalam segala keadaan” yang disampaikan kepada peserta Persekutuan Anak dan Remaja. Hasil pengabdian menunjukkan bahwa pelayanan firman Tuhan dalam konteks Kemping Paskah mampu menjadi media pembinaan iman yang efektif, tidak hanya sebagai aktivitas liturgis, tetapi juga sebagai ruang pendidikan iman yang kontekstual. Nilai-nilai Pendidikan Agama Kristen yang dikuatkan melalui kegiatan ini meliputi iman, pengharapan, kasih, kesetiaan, dan keteguhan spiritual. Kegiatan ini menegaskan bahwa pelayanan firman berbasis Matius 27:57-61 berkontribusi nyata dalam pembentukan spiritualitas dan karakter generasi muda gereja serta layak dikembangkan secara berkelanjutan dalam pelayanan gerejawi. Kata kunci: Iman;  Injil; PAK; Spiritualitas.